2018
DOI: 10.1590/s1677-5538.ibju.2017.0692
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative complications and short-term outcomes of abdominal sacrocolpopexy, laparoscopic sacrocolpopexy, and laparoscopic pectopexy for apical prolapse

Abstract: Objective:To investigate differences in perioperative complications and short-term outcomes of patients who underwent abdominal sacrocolpopexy / sacrohysteropexy, laparoscopic sacrocolpopexy / sacrohysteropexy, or laparoscopic pectopexy due to apical prolapse.Materials and Methods:A retrospective cohort study was performed on 110 patients who underwent apical prolapse surgery between January 1, 2011, and July 31, 2017. Only symptomatic uterine or vaginal vault prolapse patients with stage 2-4, according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 21 publications
2
45
1
Order By: Relevance
“…Studies comparing LS and RSC did not show differences between groups in success outcomes. Biler et al, in the study about abdominal sacropexy, LS and pectopexy, found no occurrences of de novo apical prolapse at 6 months follow‐up. In studies regarding pectopexy, we found one (2.3%) relapse of apical prolapse after pectopexy reported by Noe after 21.8 months of follow‐up and none in the initial study by Banerjee .…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Studies comparing LS and RSC did not show differences between groups in success outcomes. Biler et al, in the study about abdominal sacropexy, LS and pectopexy, found no occurrences of de novo apical prolapse at 6 months follow‐up. In studies regarding pectopexy, we found one (2.3%) relapse of apical prolapse after pectopexy reported by Noe after 21.8 months of follow‐up and none in the initial study by Banerjee .…”
Section: Resultsmentioning
confidence: 97%
“…On the basis of preoperative data, the following patients were most frequently referred for apical defect repair: POP‐Q ≥ II, postmenopausal, aged 50 to 60 years and BMI ≥ 25 kg/m 2 . The shortest laparoscopic procedure durations were 43.1 minute and 74.9 ± 34.05 minutes . (both for pectopexy); durations also depended on concomitant procedures: posterior and/or anterior defect repair and surgery for urinary incontinence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations